Analysis of a grinding efficiency in the electromagnetic mill for variable process and feed parameters - Wołosiewicz-Głąb Marta; Foszcz Dariusz; Saramak Daniel; Gawenda Tomasz; Krawczykowski Damian (E3S Web of Conferences, 2017)
Article describes issues related to the assessment of raw materials grinding efficiency in an electromagnetic mill. Application of such type of mill in grinding processes can result in measurable benefits of more efficient raw material grinding by reducing time needed to produce a product of a suitable particle size compared to conventional mills. The expected effect of application of a system based on an electromagnetic mill is to achieve a lower energy consumption of grinding process for raw material processing compared to the existing equipment used for the fine grinding. A key element of correct design of comminution circuits in processing of particular feed mineral is to identify the impact of key factors affecting the efficiency of the grinding process. The most important factors determining the efficiency of the grinding process are the time, the construction parameters of the machine, the type of grinding media used in grinding process, as well as the parameters of the feed, among others the crushing resistance or particle size. The paper presents the results of kinetic study of copper ore grinding in electromagnetic mill for variable feed particle size distribution of and different sizes of grinding media.